Potential Wind Energy Analysis in Maluku Region with Savonius Turbine using CFD Approach - Louhenapessy, Jandri; Simanjuntak, Antoni; Luhulima, Richard Benny (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
The Maluku region, also known as the Moluccas, is an archipelago in Indonesia with exceptional wind patterns ideal for wind power generation. Its strategic location between the Pacific and Indian Oceans creates strong and consistent winds due to temperature differences, making it an optimal site for wind energy production. Harnessing wind power in Maluku can significantly benefit Indonesia and the global renewable energy sector by providing a reliable and sustainable energy source to reduce greenhouse gas emissions and combat climate change. Furthermore, the development of wind power in Maluku could create new economic opportunities and incentives for the local community, promoting sustainable development and reducing the reliance on fossil fuels. A study was conducted to assess the viability of wind energy in Maluku, utilizing a Sonius turbine and computational fluid dynamics (CFD) methodology. By varying the center distance between the Savonius blade radius and its rotational axis, researchers aimed to optimize the turbine's design for maximum energy extraction. The simulations showed that turbine model design significantly impacts performance, with Model 2 outperforming Model 1 due to smoother airflow and more efficient rotation. The pressure distribution on the semicircular blades also influenced turbine performance, with Model 1 producing higher force but slower rotation speed compared to Model 2. The simulations showed that Turbine Model 1 produced a higher average force and power output compared to Turbine Model 2. According to the simulations, Model 1 showcased a higher average power output of 66.5 Watts, while Turbine Model 2 only achieved 46.6 Watts. However, Turbine Model 1 had a slower rotation speed due to its larger radius. Under consistent wind conditions, Turbine Model 1 was capable of producing 5.5% more energy than Turbine Model 2. Choosing an efficient turbine model is crucial for maximising the energy production from wind resources. The findings from this study contribute to a comprehensive understanding of the turbine's behavior and can aid in optimizing its design for maximum energy extraction.